2016
DOI: 10.18787/jr.2016.23.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nasalance in Patients with Chronic Rhinosinusitis

Abstract: Background and Objectives:This study was designed to compare the nasalance between chronic rhinosinusitis (CRS) patients and normal controls and to determine the correlation of nasalance with nasal volume, nasal resistance, CT score, and polyp score in CRS patients. Materials and Methods: This study enrolled 150 CRS patients and 154 normal adults. All subjects underwent acoustic rhinometry and rhinomanometry. Nasalance scores were measured with the nasometer. All CRS patients were graded according to the Lund-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Park et al 10 . reported a nonsignificant correlation between the polyp‐grading scores and nasalance scores.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Park et al 10 . reported a nonsignificant correlation between the polyp‐grading scores and nasalance scores.…”
Section: Discussionmentioning
confidence: 98%
“…Park et al 10 reported a nonsignificant correlation between the polyp-grading scores and nasalance scores. We attributed this observation to the distribution of disease severity in their study population.…”
Section: Influence Of Crs On Nasalance Scoresmentioning
confidence: 97%